Influence of the stress gradient on the fatigue life calculation of a martensitic high strength steel - I. Miloevic; G. Winter; F. Grn; M. Kober (Fracture and Structural Integrity)
Nowadays lifetime calculation in the high cycle fatigue region is commonly based on S/N curves which are modified by different influences to ensure accurate results. Especially the application of these models is important when small components with complex stress distributions are used. The influence of the stress distribution was considered by the stress gradient approach which is implemented in the lifetime tool FEMFAT. Specimens with diameters of D4mm and D7.5mm were used to examine the effect of the calculation modified by the stress gradient. On the one hand regarding different types of this approach it can be shown that the results fit very well compared to the testing results but on the other hand a big difference was observed when the gradient increases by smaller specimen sizes.